Reduced stress responsiveness in pregnancy: Relationship with pattern of forebrain c-fos mRNA expression - Windle, Richard J. (Elsevier/North-Holland Biomedical Press, 2010)
Stress-induced activation of the hypothalamo-pituitary-adrenal (HPA) axis is known to be attenuated during late pregnancy and throughout lactation. To investigate the neural basis of this stress hyporesponsiveness we examined the changes in the restraint-induced HPA response and accompanying forebrain expression of c-fos mRNA that occur in rats between days 16 (D16) and 19 (D19) of gestation, times associated with declining levels of progesterone, a potential mediating factor. Compared to D16, the D19 group showed a significantly attenuated release of ACTH following 30 min restraint. This reduced HPA response was accompanied by significantly lower levels of restraint-induced c-fos mRNA expression in the hypothalamic paraventricular nucleus. Other areas of the forebrain, including medial amygdala, piriform cortex, and ventrolateral septum, showed low c-fos mRNA expression in non-stressed (control) animals and a large increase following restraint, the magnitude of which was similar between D16 and D19 animals indicating no involvement in the differential HPA response to stress. However, a markedly different pattern of c-fos mRNA expression was observed in other brain areas, including barrel cortex and CA1 ventral and CA3 regions of the ventral hippocampus: D19 animals had low control expression which was increased by restraint, but D16 control animals had raised c-fos mRNA expression which was not further elevated by stress. These data demonstrate that region-specific changes in basal and stress-induced cellular activity occur during a period of late gestation coincident with attenuated HPA responsiveness. These changes in neuronal activity may contribute to the adaptive processes that prepare the mother for parturition and lactation.